THE FACTORS OF ITS DEVELOPMENT AND INTRODUCING THE PROFESSION IN SECONDARY SCHOOLS - Nigora Akbarovna Sharapova (European Science Publishing, 2024)
This article presents ideas on the methods of organizing and conducting vocational orientation work with students of general education schools.
Keywords: profession, creative thinking, conscious work preparation, formation of thinking in primary education, educational product.